Effect of Cold Atmospheric Pressure Plasma Coupled with Resin-Containing and Xylitol-Containing Fluoride Varnishes on Enamel Erosion - Zahra Khoubrouypak; Mahdi Abbasi; Elham Ahmadi; Niyousha Rafeie; Marjan Behroozibakhsh (Hindawi Limited, 2021)
Purpose. Considering the suggested advantages of cold atmospheric plasma (CAP) in increasing the fluoride uptake by the enamel, this study aimed to assess enamel erosion following the application of helium CAP and two types of fluoride varnishes. Methods. The microhardness of 70 bovine enamel specimens was measured using a Vickers hardness tester. The specimens were randomly divided into 7 groups (n = 10): control, CAP (P), resin-containing fluoride varnish (RF), CAP + resin-containing fluoride varnish (PRF), fluoride varnish (F), CAP + fluoride varnish (PF), and erosion (E). The specimens in the control and erosion groups did not receive CAP or fluoride varnish. All specimens underwent erosive challenge 4 times/day using hydrochloric acid and artificial saliva except for the control specimens that remained in distilled water during the course of the study. After 5 days of erosive challenge, microhardness was measured again, and the percentage of microhardness change was calculated. Surface roughness of two specimens in each group was assessed by atomic force microscopy (AFM). Data were analyzed using one-way ANOVA followed by Tamhane's post-hoc test. Results. The percentage of microhardness change in all groups was significantly higher than that of the control group. All groups showed significantly lower percentage of microhardness change compared with the E group except for the P group; no significant difference was noted in microhardness change of P and E groups. Other experimental groups had no significant difference with each other. Surface roughness was the highest in PRF and the lowest in the F group. Conclusion. CAP application had no significant effect on increasing the enamel resistance to erosion. However, enamel resistance to erosion increased significantly after fluoride varnish application alone or fluoride varnish application combined with CAP. No significant difference was noted between the two types of varnishes in this regard. CAP increased the surface roughness while fluoride varnish application alone decreased the roughness.